Capital Factors of Rubella Vaccination Behaviour among the Parents in Bangladesh: A PLS-SEM Analysis - Kalam Azad, Abul (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study predicts rubella vaccination behavior of the parents in Bangladesh based on CAPSES model : Human Capital (HC), Material Capital (MC) and Social Capital (SC). A sample size of 72 parents was determined to collect data. The study employed structured questionnaire technique based on 5 point-Likert scale. Then, the study used SmartPLS software (Windows Version-3) to analyze both the measurement and structural models. The study findings lead to this proposition that the higher the CAPSES ranks of the parents, the more likely they will vaccinate their children against MR. On the contrary, the lower the CAPSES rank of the parents, the less likely they will vaccinate their children against MR. Overall, the models have predictive power and relevance in the respective models (R2of RVB1= 0.862) was found to be more substantial compared to two other CAPSES models (R2 of RVB2 = 0.240 and R2 of RVB3 = 0.181).